Momentos críticos no corpo - Ramírez, Xochiquetzaly Yeruti de Avila (2014)
This work derives from the clinical observation of patients under treatment in a hospital institution, going through a critical moment. Bringing together clinical report and metapsychology-making of the case, a panel is presented following the postulates of the Clincal Method and Fundamental Psychopathology. It delves into the psychic dimensions implied in cases of: acute appendicitis, multiple sclerosis, ghost limb syndrome, and amnesia and blindness due to cranioencephalic post-multitraumatism. We speculate that critical moments are enigmatic forms of reorganization of the body seeking a harmonic. Organic disorders due to illness or accident are possible conditions to reach new balances. We conjecture that reordering in the body is an answer to the paradigm of creative philo-ontogenetic solutions. Introducing into the transference the experience of feeling alive constitutes the element of therapeia, aiming the reestablishment of the vital rhythm of the body, its pulsional harmonics